Extended spectrum β-lactamase producers among nosocomial Enterobacteriaceae in Latin America - Manuel Guzmán-Blanco; Jaime A. Labarca; Maria Virginia Villegas; Eduardo Gotuzzo (Brazilian Journal of Infectious Diseases, 2014)
To review the epidemiology of nosocomial extended spectrum β-lactamase-producing Enterobacteriaceae in Latin America, a systematic search of the biomedical literature (PubMed) was performed for articles published since 2005. Rates of nosocomial infections caused by extended spectrum β-lactamase-producing Enterobacteriaceae in Latin America have increased since 2005. Up to 32% of Escherichia coli and up to 58% of Klebsiella pneumoniae isolates are extended spectrum β-lactamase-positive, rates that are higher than in other world regions. From a region-wide perspective, 11–25% of E. coli isolates and 45–53% of K. pneumoniae isolates were nonsusceptible to third-generation cephalosporins. At the country level, there was a wide range in Enterobacteriaceae resistance rates to third-generation cephalosporins, with especially high rates of resistance to E. coli in Guatemala, Honduras, and Mexico, and high resistance rates to Klebsiella spp. in Argentina, Brazil, Chile, Guatemala, Honduras, and Paraguay. Susceptibility of extended spectrum β-lactamase-producing Enterobacteriaceae to cefepime, fluoroquinolones, ampicillin/sulbactam, aminoglycosides, and piperacillin/tazobactam has also been compromised, leaving the carbapenems, tigecycline, and colistin as the only antibiotics with >90% susceptibility rates. There is a steady increase in the prevalence and types of extended spectrum β-lactamases produced by Enterobacteriaceae isolates in Latin American hospitals (particularly CTX-Ms), suggesting endemic conditions overlaid by clonal outbreaks. Appropriate treatment decisions and infection control strategies informed by surveillance of regional and local susceptibilities and mechanisms of resistance are required to mitigate this major public health concern. Keywords: Escherichia coli, Klebsiella, Latin America, Bacterial resistance